2017
DOI: 10.1038/onc.2017.228
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor Pdcd4 attenuates Sin1 translation to inhibit invasion in colon carcinoma

Abstract: Programmed cell death 4 (Pdcd4), a tumor invasion suppressor, is frequently down-regulated in colorectal cancer and other cancers. In this study, we find that loss of Pdcd4 increases the activity of mammalian target of rapamycin complex 2 (mTORC2) and thereby upregulates Snail expression. Examining the components of mTORC2 showed that Pdcd4 knockdown increased the protein but not mRNA level of stress-activated-protein kinase interacting protein 1 (Sin1), which resulted from enhanced Sin1 translation. To unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 49 publications
6
56
0
1
Order By: Relevance
“…Previous studies have revealed the cell cycle inhibitory and apoptosis-inducing roles of PDCD4, so PDCD4 has been regarded as a tumor suppressor [9][10][11][12]. The downregulation of PDCD4 is observed in different types of cancer, such as colorectal carcinoma [13], prostate cancer [14], glioblastoma [15], lung cancer [16], and hepatocellular carcinoma [12]. Several mechanisms underlying the downregulation of PDCD4 have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed the cell cycle inhibitory and apoptosis-inducing roles of PDCD4, so PDCD4 has been regarded as a tumor suppressor [9][10][11][12]. The downregulation of PDCD4 is observed in different types of cancer, such as colorectal carcinoma [13], prostate cancer [14], glioblastoma [15], lung cancer [16], and hepatocellular carcinoma [12]. Several mechanisms underlying the downregulation of PDCD4 have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…MCs isolated from fibrotic lung allografts demonstrated significantly higher mSin1 expression compared with MCs isolated from normal lung allografts. Increased expression of mSin1 has been linked to metastatic and activated behavior in cancer cells (31)(32)(33). mSin1 was shown to be up-regulated in non-small-cell lung cancer (31) as well as in metastatic carcinoma of the colon (33) and the liver (32), with mSin1 suppression inhibiting proliferation, migration, and invasion rates.…”
Section: Discussionmentioning
confidence: 99%
“…主调节基因肝X受体-α(liver X receptor-α, LXR-α)的表 达, 促进肥胖所导致慢性炎症以及胰岛素抵抗 [48] . 最 近Wang等人 [49] 的研究证明, 在结肠癌模型中PDCD4…”
Section: 发现 Pdcd4通过eif4a依赖的方式抑制脂质代谢的unclassified